SKYHOOK CHURCHILL 1968. - Cravaack,Charles H.; Pappas,Thomas (1969)
The program provided thirty-two balloons for at least twenty-five flights from Fort Churchill, Manitoba and one flight from Resolute Bay, N.W.T. A supplementary program, funded for two months, was later performed with a reduced crew at Lynn Lake, Manitoba. The contract was funded for a period of 60 days in the field at Fort Churchill. Raven Industries provided a field crew, suspension and rigging hardware, aircraft tracking, gondola recovery, parachutes, balloon control instrumentation, telemetry, down-range instrumentation, and reports and documentation as necessary. This report describes individual flights, equipment used, flight data, and problems encountered throughout the 1968 Skyhook program. (Author) See also 1967 report, AD-681 337.